Can AI Reduce Unnecessary Medical Testing? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2016)
Artificial intelligence (AI) is rapidly transforming the healthcare landscape, offering unprecedented opportunities to enhance diagnostic accuracy, streamlin...
Keywords: AI in Clinical Decision Support; Reduce; Unnecessary; Medical; Artificial Intelligence; Machine Learning; Healthcare